Integrated modelling to support decision-making for marine social–ecological systems in Australia. (26th May 2017) - Melbourne-Thomas, Jessica; Constable, Andrew J; Fulton, Elizabeth A; Corney, Stuart P; Trebilco, Rowan; Hobday, Alistair J; Blanchard, Julia L; Boschetti, Fabio; Bustamante, Rodrigo H; Cropp, Roger; Everett, Jason D; Fleming, Aysha; et al.
Abstract: Policy- and decision-makers require assessments of status and trends for marine species, habitats, and ecosystems to understand if human activities in the marine environment are sustainable, particularly in the face of global change. Central to many assessments are statistical and dynamical models of populations, communities, ecosystems, and their socioeconomic systems and management frameworks. The establishment of a national system that could facilitate the development of such model-based assessments has been identified as a priority for addressing management challenges for Australia's marine environment. Given that most assessments require cross-scale information, individual models cannot capture all of the spatial, temporal, biological, and socioeconomic scales that are typically needed. Coupling or integrating models across scales and domains can expand the scope for developing comprehensive and internally consistent, system-level assessments, including higher-level feedbacks in social–ecological systems. In this article, we summarize: (i) integrated modelling for marine systems currently being undertaken in Australia, (ii) methods used for integration and comparison of models, and (iii) improvements to facilitate further integration, particularly with respect to standards and specifications. We consider future needs for integrated modelling of marine social–ecological systems in Australia and provide a set of recommendations for priority focus areas in the development of a national approach to integrated modelling. These recommendations draw on—and have broader relevance for—international efforts around integrated modelling to inform decision-making for marine systems.